Cloning, expression and purification of D-Tyr-tRNATyr-deacylase from Thermus thermophilus - Rybak, M.Yu.; Kovalenko, O.P.; Kryklyvyi, I.A.; Tukalo, M.A. (Вiopolymers and Cell, 2015)
D-Tyr-tRNATyr-deacylase (DTD) is a conservative enzyme, found in all domains of life, which ensures an additional checkpoint in the recycling of misaminoacylated D-Tyr-tRNATyr. DTD is capable of accelerating the hydrolysis of the ester linkage of D-Tyr-tRNATyr producing a free tRNA and D-tyrosine, thereby preventing an incorrect incorporation of D-amino acids into proteins. Deacylase distinguishes between D- and L-aminoacyl moieties and does not hydrolyze L-aminoacylated tRNA. The structural bases of this specificity and the mechanism of D-aminoacyl-tRNA hydrolysis are poorly understood. Aim. To clone D-Tyr-tRNATyr-deacylase from T. thermophilus (DTDTT), optimize the conditions for its expression in E.coli and develop an efficient purification procedure yielding the high quality enzyme suitable for the structural and functional studies. Methods. For amplification of DTD gene from T. thermophilus genomic DNA and its cloning into the pProEXHTb expression vector modern techniques were applied. Purification of the recombinant DTD protein was done with three types of column chromatography. His-tag was cleaved out from DTD by TEV protease. The cleavage was confirmed by Western blot analysis with anti-His-tag antibodies. Molecular weight of purified DTDTT was determined by the gel-filtration. Results. The expression construct pProEXHTb, containing DTD sequence from T. thermophilus, was obtained and successfully expressed in the BL21(DE3)pLysS E.coli strain. The protein of interest was purified to homogeneity by the combination of affinity (Ni-NTA), anion-exchange (Q-Sepharose) and size-exclusion (Superdex S 200) chromatographies. 2 mg of more than 90% pure recombinant DTD can be obtained from 1 L of bacterial culture. Molecular weight of purified DTD from T. thermophilus was determined to be 32 kDa, suggesting its dimeric structure. Conclusions. The pProEXHTb expression vector can be used for expression of DTD from T. thermophilus. The preparative amounts of DTD can be obtained after the three-step chromatographic procedures and used for further functional and structural studies. D-Тир-тРНКТир-деацилаза (DTD) є консервативним білком, знайденим у всіх царствах живої природи, що забезпечує додатковий корегувальний етап гідролізу помилково аміноацильованих субстратів D-Тир-тРНКТир DTD здатна приcкорювати гідроліз ефірного зв’язку в комплексі D-Тир-тРНКТир, утворюючи вільну тРНК та D-Тир, таким чином попереджуючи включення D-амінокислот до білків. Деацилаза розрізняє D- та L-аміноацильні залишки в аміноацильованій тРНК та не гідролізує останні. Структурні основи такої специфічності та механізм гідролізу D-аміноацил-тРНК за участі DTD є недостатньо зрозумілими. Мета. Клонувати D-Тир-тРНКТир-деацилазу з T. thermophilus (DTDTT), оптимізувати умов її експресії в E. coli, розробити ефективний метод очищення з високим виходом високоякісного ферменту, для структурних та функціональних досліджень. Методи. Ампліфікацію та клонування в pProEXHTb DTD гена геномної ДНК T. thermophilus проведено за стандартними молекулярно-біологічними методами. Очистку рекомбінантного DTD білка проводено хроматографічно. Залишки гістидину відщеплено від DTD протеазою вірусу тютюну (TEV), ефективність реакції перевірено Вестерн-блот аналізом з анти-His-антитілами. Молекулярну масу очищеної DTDTT визначено гель-фільтрацією. Результати. Отримана конструкція pProEXHTb, що містить DTD послідовність з T. thermophilus, експресовано в E.coli штаму BL21(DE3)pLysS. Цільовий рекомбінантний білок виділено і очищено комбінацєю хроматографій: афінної (Ni-NTA), аніон-обмінної (Q-Sepharose) та гель-фільтрації (Superdex S 200) до чистоти 90%. Вихід рекомбінантної DTD склав 2 мг з одного літру культури. Визначена молекулярна маса очищеної DTD з T. thermophilus – 32 кДа свідчить на користь її димерної структури. Висновки. Отриманий вектор pProEXHTb, що містить DTD з T. thermophilus і підібрані умови очистки дозволяють отримати рекомбінантний DTD в кількостях достатніх для подальших структурно-функціональних досліджень. D-Тир-тРНКТир-деацилаза (DTD) является консервативным белком, найденным во всех царствах живой природы, обеспечивающим дополнительный корректирующий этап гидролиза ошибочно аминоацилированных субстратов D-Тир-тРНКТир. DTD ускоряет гидролиз эфирной связи в комплексе D-Тир-тРНКТир, предупреждая, таким образом, ошибочное включение D-аминокислот в белки. Деацилаза различает D- и L-аминоацильные остатки в аминоацилированной тРНК и не гидролизирует последние. Структурные основы такой специфичности и механизм гидролиза D-аминоацил-тРНК при участии DTD являются недостаточно изученными. Цель. Клонировать D-Тир-тРНКТир-деацилазу из T. thermophilus (DTDTT), оптимизировать условия её экспрессии в E. coli и разработать эффективный, с высоким выходом высококачественного фермента, метод очистки. Методы. Для амплификации и клонирования в pProEXHTb гена DTD геномной ДНК T. thermophilus использованы стандартные молекулярно-биологические методы. Очистку рекомбинантного DTD белка проводили хроматографически. Остатки гистидина отщепили протеазой вируса табака (TEV), еффективность реакции проверили Вестерн-блот анализом с анти-His-антителами. Молекулярный вес очищенной DTDTT определили гель-фильтрацией. Результаты. Полученная конструкция pProEXHTb, содержащая DTD последовательность T. thermophilus, экспрессирована в клетках E. coli штамма BL21(DE3)pLysS. Последовательными хроматографиями: афинной (Ni-NTA), анион-обменной (Q-Sepharose) и гель-фильтрации (Superdex S 200) получен гомогенный белок с чистотой более 90 %. Разработанная методика позволяет получить до 2 мг целевого белка / 1 л культуры. Определенный молекулярный вес очищенной DTD из T. thermophilus – 32 кДа свидетельствует о ее димерной структуре. Выводы. Полученная конструкция pProEXHTb, содержаащя DTD последовательность T. thermophilus и подобранные условия очистки позволяют получить рекомбинантный DTD для дальнейших структурно-функциональных исследований.